Peran Indikator Kinerja Pelaksanaan Anggaran Sebagai Acuan Laporan Keuangan pada Instansi - Rita Myrna; Annisya Verena Justicia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
What is meant by IKPA? The meaning of IKPA (Budget Implementation Performance Indicators) is based on the Regulation of the Director General of Treasury, namely Regulation Number PER-5/PB/2022 which discusses IKPA or Budget Implementation Performance Indicators, which is an indicator determined by the Ministry of Finance, namely the State General Treasurer (BUN) which has functions as a measuring tool regarding the quality of performance in implementing budgets for State Ministries/Institutions through the quality of budget planning implementation, the quality of budget implementation, and the quality of the results of implementing a financial report budget in each period. In principle, the IKPA assessment is carried out with the aim of assessing the performance of budget implementation in 1 period, namely one year. In the process of monitoring to create maximum performance achievements, the Agency Office carries out mentoring activities and an evaluation process for IKPA work units regarding the implementation of the budget that has been provided by the Directorate General of Treasury which is integrated into Online Mentoring (OM) which will be realized in a form of measurement and describes the performance of the work unit regarding the quality of budget planning, the quality of the budget implementation process, and also the quality of the results of budget implementation. Based on the applicable law in Minister of Finance Regulation Number 195/PMK.05/2018, which contains Monitoring, Supervision and Evaluation regarding the Expenditure Budget Implementation process that has been implemented. The second regulation is Regulation of the Director General of Treasury Number PER-5/PB/2022 which discusses various Technical Instructions for Assessment of Performance Indicators for Ministry/Agency Budget Implementation. Budget Implementation Performance Indicators have many aspects and also IKPA Indicators that must be known, namely Quality of Budget Planning, Quality of Budget Implementation, Quality of Implementation Results